Tumor cells proliferation and migration under the influence of their microenvironment - Avner Friedman; Yangjin Kim (Mathematical Biosciences and Engineering)
It is well known that tumor microenvironment affects tumor growth and metastasis:Tumor cells may proliferate at different rates and migrate indifferent patterns depending on the microenvironment in which they are embedded.There is a huge literature that deals with mathematical models oftumor growth and proliferation, in both the avascular andvascular phases. In particular, a review of the literature of avasculartumor growth (up to 2006) can be found in Lolas [8](G. Lolas, Lecture Notes in Mathematics, Springer Berlin / Heidelberg,1872, 77 (2006)).In this article we report on some of our recent work. We considertwo aspects, proliferation and of migration, and describemathematical models based on in vitro experiments. Simulations ofthe models are in agreement with experimental results. The modelscan be used to generate hypotheses regarding the developmentof drugs which will confine tumor growth.